CLINICOPATHOLOGIC FEATURES OF HUMAN PAPILLOMAVIRUS–ASSOCIATED ORAL EPITHELIAL DYSPLASIA - Henley-Smith, R; Gregson-Williams, H; Odell, E; Thavaraj, S (Oral surgery, oral medicine, oral pathology and oral radiology, 2021)
There has been growing acceptance by the oral pathology community that high-risk human papillomavirus (HPV) is associated with a subset of oral epithelial dysplasias (OEDs), but there is lack of consensus on the diagnostic criteria for HPV OED. This study describes the clinicopathologic features of this disease with the intention of adding to the current pool of knowledge to clarify diagnostic criteria and elucidate its clinical significance. Automated p16 and viral capsid immunohistochemistry, as well as high-risk HPV DNA and RNA in situ hybridization were undertaken in 71 archival samples from 40 patients diagnosed with HPV OED and 11 samples demonstrating similar histomorphological features. Ploidy analysis was undertaken on a subset of samples. The male:female ratio was 3.4:1. Five patients presented with adjacent associated invasive carcinoma, and in 4 patients there was subsequent malignant transformation. Histologic features of viral infection did not consistently colocalize with p16, and DNA or RNA in situ hybridization and were also present at varying degrees in the cases deemed HPV-negative. Capsid protein was present in 11 cases. Seven cases were DNA negative but assessed RNA positive. Of the cases subject to ploidy analysis, 9 were diploid and 6 were aneuploid. Two cases were reclassified as papillomas. Standardized diagnostic criteria are required to differentiate HPV OED from histologic mimics. Further research is necessary to determine the histologic and ancillary factors that may be useful in predicting malignant transformation.